Building Connections During a Time of Global Change: An International Snapshot of Virtual Exchange - Bhandari , Rajika; Kastler, Kyle (International Higher Education, 2022)
Virtual exchange has witnessed unprecedented growth in recent years, yet much remains to be known about types of programs globally; characteristics of participants and content of programs; and countries engaged in these activities. Based on a 2021 survey of virtual exchange, this article presents key findings about the landscape of global virtual exchange, while sharing lessons learned and implications for implementing virtual exchange. Further, the variable impact of COVID-19 on virtual exchange is also examined.